Comparison of pressure-assist silver sintering to tin silver solder alloy as die attach material in high power semiconductor / Erik Nino Tolentino - Erik Nino, Tolentino (2020)
The research is focused on pressure-assisted silver sintering material that is compared to tin silver solder alloy paste as used in power electronics. Material characterization, electrical tests, and reliability tests were conducted in the experiment. After drying process, it was observed that the Ag sintering paste height was reduced to approximately 40 percent. Die attach shear test showed that the average reading is about from 200 to 600 grams which are already enough to hold the dice before proceeding to the pressure sintering process. X-ray revealed that the void percent for SnAg paste sample is about 1.5 percent while pressure-assist Ag sintering paste sample doesn’t have any voids after build. Scanning electron microscopy (SEM) microstructure analysis showed that the SnAg solder sample will form Sn-Ag and Sn-Cu intermetallic compounds between the solder alloy after reflow. For Ag sintering sample, it was observed that the die-to-Ag sintering and Ag sintering-to-DBC joint were properly executed. Agglomeration and aggregation take over in Ag-Ni sinter particles. The diffusion of Ag sintering material in die TiNiAg back metal and Cu DBC was also detected. This acquiring a mechanical lock that forms solid-state diffusion in the system. Electrical test reading shows that the VGE and VCES measurement reading for Ag sintering sample is lower compared to SnAg solder alloy sample. The thermal shock and temperature cycle test that were performed in both samples are comparable in performance. The power cycle test runs on the other hand give the opposite output response. SnAg solder sample only reaches the 20000 cycles but failed at 40000cyle. However, Ag sintering sample reaches 60000 cycle without failure.